2014
DOI: 10.1002/rra.2849
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of River Contamination Derived From Acid Mine Drainage Using Airborne Imaging Spectroscopy (HyMap Data, South‐West Spain)

Abstract: Imaging spectroscopy is used in this work as an essential mapping tool to monitor changes in contaminated river sediments. Multidate hyperspectral image data (HyMap) are utilized to identify spatial mineral patterns, to detect temporal changes in mineralogy and to link these changes with geochemical processes and short‐term climate characteristics. River sediments contaminated by acid mine drainage are covered by crusts with variably hydrated iron sulphate. The mineralogy of the crusts and the grain size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…A pH value around 3 favors the hydrolysis and precipitation of Fe 3+ ions, which takes place usually in the form of very fine-grained schwertmannite (with traces of jarosite) [17]. These minerals are mineralogically meta-stable and usually are transformed into goethite or hematite [47].…”
Section: Hydrogeochemical Mapsmentioning
confidence: 99%
“…A pH value around 3 favors the hydrolysis and precipitation of Fe 3+ ions, which takes place usually in the form of very fine-grained schwertmannite (with traces of jarosite) [17]. These minerals are mineralogically meta-stable and usually are transformed into goethite or hematite [47].…”
Section: Hydrogeochemical Mapsmentioning
confidence: 99%
“…Following the Leadville work, many other similar studies were conducted demonstrating the use of imaging spectrometers for mapping secondary minerals related to acid drainage (Kruse et al 1989;Fenstermaker and Miller 1994;King et al 1995;Peters et al 1995;Farrand 1997;Farrand and Harsanyi 1997;Lopez-Pamo et al 1999;Rockwell et al 2005;Pearson et al 1997;Kemper and Sommer 2004 and many others). Of particular interest, are the studies conducted by Zabcic et al (2014) and Buzzi et al (2016) who carried out the mapping of efflorescent salts, many of which have spectrally diagnostic features. For example, malenterite has a broad double crystal field transition absorption feature at 892 and 1150 nm related to ferrous iron and a smaller absorption feature at 434 nm related to Fe 3+ -O charge transfer feature (Crowley et al 2003).…”
Section: Acid Drainagementioning
confidence: 99%
“…IS has unique contributions to make via its ability to provide quantitative diagnostic information to better inform assessments and monitor hazards and their related threats. In the last two decades, with the increasing availability of IS particularly in the visible (VIS) to shortwave infrared (SWIR) (400-2500 nm) range mainly from airborne platforms, some convincing studies have demonstrated its remarkable effectiveness (for acid drainage see Buzzi et al 2016;Davies and Calvin 2017;Farrand 1997;Farrand and Harsanyi 1997;Fenstermaker and Miller 1994;Kemper and Sommer 2004;King et al 1995;Kopačková 2014;Kruse et al 1989;Lopez-Pamo et al 1999;Ong and Cudahy 2014;Pearson et al 1997;Peters et al 1995;Shi et al 2014a, b;Swayze et al 1996Swayze et al , 2000Rockwell et al 2005;Zabcic et al 2014; for fugitive dust see Clark et al 2006;Chudnovsky et al 2009Chudnovsky et al , 2011Ong et al 2003aOng et al , b, c, 2008Ong 2013;Pascucci et al 2012; for hydrocarbon contamination see Beland et al 2016;Clark et al 2010;Khanna et al 2013;Kokaly et al 2013;Peterson et al 2015; for atmospheric emissions see Bradley et al 2011;Dennison et al 2013;Deschamps et al 2013;Franke et al 2009;Frankenberg et al 2016;Frassy et al 2014;Krautwu...…”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact that the actual spectral data are easily affected by the environment, the existing spectral database is not sound enough, and the ground truth measurement in remote and harsh natural conditions is almost impossible to achieve, making the acquisition of a priori spectral information becomes the difficulty of the target supervised classification algorithm. With the continuous advancement of remote sensing technology, its effect on mineral remote sensing monitoring has become increasingly significant 1,2 …”
Section: Introductionmentioning
confidence: 99%